Introduction to acute and ambulatory care pharmacy practice - Holdford, David A. (ASHP, 2017)
Introduction to Hospital & Health-System Pharmacy Practice was a text that introduced students of all ages to professional pharmacy practice in the healthƯ system organization. Overall, it is an excellent introductory text and useful reference to be included in any practitioner's library.""--A review in the Journal of Pharmaceutical Technology ""This book is highly recommended and will be an excellent resource for students as well as pharmacists"" From a 2011 review in the American Journal of Pharmaceutical Education Building on the success of the previous edition, this new edition of ...